1930
DOI: 10.1037/h0071341
|View full text |Cite
|
Sign up to set email alerts
|

Personality and character tests.

Abstract: About thirty of the reports appearing in 1929 were based on new tests and techniques. Very little was written about ratings, but the use of controlled observation as a scientific instrument was indicated in eleven studies. There is an increasing tendency to use existing techniques for the solution of problems. That is, the center of interest is gradually shifting from tools to problems. The total number of articles is far smaller than for several years.Summaries. In addition to the writers' summary (71), Burnh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1930
1930
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This work went by various names-temperament and character also were used. By 1930, May and Hartshorne (1926;May, Hartshorne, & Welty, 1927, 1928, 1930, as cited in Viteles, 1932 had produced five reviews in the Psychological Bulletin in which they showed, for example, what is now called "reliability" or "conscientiousness" was a holistic personality construct they called "consistency." Consistent or integrated individuals, they proposed based on evidence, were predictable in their behavior while inconsistent individuals were not.…”
Section: In the Beginning-the 1920s And 1930smentioning
confidence: 99%
“…This work went by various names-temperament and character also were used. By 1930, May and Hartshorne (1926;May, Hartshorne, & Welty, 1927, 1928, 1930, as cited in Viteles, 1932 had produced five reviews in the Psychological Bulletin in which they showed, for example, what is now called "reliability" or "conscientiousness" was a holistic personality construct they called "consistency." Consistent or integrated individuals, they proposed based on evidence, were predictable in their behavior while inconsistent individuals were not.…”
Section: In the Beginning-the 1920s And 1930smentioning
confidence: 99%
“…Since the early days of applied psychology, researchers have been interested in personality and vocational interests, as well as the association between these two domains (cf. May, Hartshorne, & Welty, 1927, 1928, 1929, 1930). Yet, as has often been the case in psychological research, the lack of comprehensive taxonomies long stalled systematic reviews of their interrelation.…”
Section: Introductionmentioning
confidence: 99%
“…May and Hugh Hartshorne published their bibliography, Personality and Character Tests, for the years 1920-1925, which included a section specifically devoted to the measurement of morality; this bibliography was updated yearly (cf. May, Hartshorne, & Welty, 1927). Young (1927) and Watson (1927) followed with similar lists.…”
Section: Development Of Morality Testsmentioning
confidence: 99%
“…According to Watson (1927), these tests showed little usefulness, because the conclusions were "uniformly disappointing" (p. 79). It was likewise reported that Fernald's (1912) test, which was included in Kohs's battery, did not serve its purpose (May, Hartshorne, & Welty, 1927); neither did the Presseys' (1919) cross-out section (Collins, 1925;Lowe & Shimberg, 1925). Overall, Collins noted that better educated students scored higher and, therefore, Kohs's battery measured intelligence more than anything else.…”
Section: Development Of Morality Testsmentioning
confidence: 99%